Pemilihan Pemasok Drum Pelumas Industri Menggunakan Fuzzy Analytical Hierarchy Process (Studi Kasus: PT. Pertamina Pusat dan Production Unit Gresik) - D. A. Mardhikawarih; Wakhid Ahmad Jauhari; Cucuk Nur Rosyidi (Performa: Media Ilmiah Teknik Industri, 2012)
PT Pertamina Lubricant unit has the largest lubricants production units that PUG (Production UnitGresik). As part of the manufacturing industry often experience problems on PUG electoral system and assessment of supplier. Inaccuracies in selecting supplier results the selected supplier failed to deliver an order continually. One of the solutions of this problem is to improve the supplier selection system. Therefore, this research aims to develop supplier selection model with involves the Pertamina Oil Centre and PUG. An earlier stage of the research is to determine the criteria and subcriteria of the supplier selection obtained through Questionnaires I. The second stage was composing the hierarchy of the problem that was found in the company. The third stage was composing Questionnaires II wich translating AHP scale into triangular fuzzy number. The fourth stage aggregated appraisement of the whole of the respondents. The fifth stage calculated the value of the degree of possibility. The final stage calculated the value of consistency ratio from the opinion of the decision makers. After criteria and sub criteria of the selection and assessment suppliers has been developed. Then it used to choice the supplier of industrial lubricant drum. This research resulted eight criteria selection and assessment of supplier quality criteria, price, delivery, service, innovation, safety and working environment, flexibility, organization with a total combined all the criteria as much as sub criteria 29 sub criteria. The highest weighting is quality’s criteria (1.00), while the highest one is claims replacement good’s subcriteria (1.00). The results from supplier assessment indicated that the supplier Y was the chosen supplier